Sliding Mode Controller based Maximum Power Point Tracking of DC to DC Boost Converter - Anusuyadevi R; Suresh Pandiarajan P; Muruga Bharathi J (Institute of Advanced Engineering and Science, 2013)
A sliding mode controller is used to estimate the maximum power point as a reference for it to track that point and force the PV system to operate in this point. In sliding mode control, the trajectories of the system are forced to reach a sliding manifold of surface, where it exhibit desirable features, in finite time and to stay on the manifold for all future time. The load is composed of a battery bank. It is obtained by controlling the duty cycle of a DC-DC converter using sliding mode control. This method has the advantage that it will guarantee the maximum output power possible by the array configuration while considering the dynamic parameters solar irradiance and delivering more power to charge the battery. The proposed system with sliding mode control is tested using MATLAB / SIMULINK platform in which a maximum power is tracked under constant and varying solar irradiance and delivered to the battery which increasing the current that is charging the battery and reduces the charging time.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.2289